The Touching Test: AI and the Future of Human Intimacy. - Reineke, Martha J. (Contagion: Journal of Violence, Mimesis & Culture, 2022)
The article explores the capacity of artificial intelligence (AI) for human intimacy and the potential of human love relationships with humanoid robots. Topics discussed are traits that a robot will offer to its human partner, realness of AI agent as human in the film "Ex Machina" based on the criteria of mimesis, vulnerability, nonautonomous desire and capability for violence, and the Turing test and touching test for robots in order to possess all attributes necessary to pass as human.